On revisions of Šarić's Bible translations - Ruben Knežević (Kairos (English Ed.), 2007)
In this paper, revisions of Šarić's translation of the Holy Scriptures are analyzed, on the occasion of the release of the latest revision, published by the Croatian Bible Society. Following the introductory notes, the first chapter analyses points of contact between Šarić's Bible translation and preferred Protestant translation choices. In the second chapter all previous revisions of various Croatian translations of the Bible are described. In the third chapter, all revisions of Šarić's translation are presented, from the historical and translation-methodology aspect: from the revision by Luka Brajnović (1959-60) in Madrid, the revision by publisher "Caritas Croata" (1966 - 1969) in Salzburg, and the revision by Đuro Martinjak (1988), up to the most recent revision, prepared by the Croatian Bible Society (2006). In the fourth chapter, on the basis of the text of the Epistle of Jude, specific revising interventions are analyzed and compared, in all of the mentioned revisions of Šarić's translation, in relation to his original edition (1942.). The original Šarić translation and the texts of certain revisions are placed in parallel columns, together with the Greek Critical New Testament text, and the author presents his comments under every line. In the fifth chapter, it is determined, in conclusion, that the revision by the Croatian Bible Society, despite some imperfections, truly has the character of a "first revised edition," because all the former revisions mostly made corrections of a limited scope.